Medical Management of Hereditary Optic Neuropathies - La Morgia, Chiara; Carbonelli, Michele; Barboni, Piero; Sadun, Alfredo Arrigo; Carelli, Valerio (Frontiers in Neurology, 2014)
Hereditary optic neuropathies are diseases of the optic nerve. The most common are mitochondrial hereditary optic neuropathies, i.e. the maternally inherited Leber’s Hereditary Optic Neuropathy (LHON) and Dominant Optic Atrophy (DOA). They both share a mitochondrial pathogenesis that leads to the selective loss of retinal ganglion cells and axons, in particular of the papillo-macular bundle. Typically, LHON is an acute/subacute loss of central vision associated with impairment of color vision and swelling of retinal nerve fibers followed by optic atrophy. DOA, instead, is characterized by a childhood-onset and slowly progressive loss of central vision, worsening over the years, leading to optic atrophy. The diagnostic workup includes neuro-ophthalmologic evaluation and genetic testing of the three most common mitochondrial DNA mutations affecting complex I (11778/ND4, 3460/ND1 and 14484/ND6) for LHON and sequencing of the nuclear gene OPA1 for DOA. Therapeutic strategies are limited including agents that bypass the complex I defect and exert an antioxidant effect (idebenone). Further strategies are aimed at stimulating compensatory mitochondrial biogenesis. Gene therapy is also a promising venue that still needs to be validated.